Students’ Conceptions of the Nature of Geography: Results of an Explorative Interview Study - Bette, Julian; Schubert, Jan Christoph (Journal of Geography Education, 2012)
The establishment of national educational standards and the re-orientation towards the achievement of competencies as the main goal of geographic education have raised the importance of meta-cognitive knowledge on geography as a subject. While in the area of school politics a general, yet controversial understanding of the subjects’ nature has been developed through the national educational standards, only little is known by now about pupils’ conceptions on geography as a subject. In order to examine the students’ perspective on geography, semi-structured interviews were conducted in the study followed by a qualitative content analysis of the transcribed interviews. The results show big differences between the students’ and the scientific concept of geography. However, starting points for relating the different concepts to each other were recognized as well.